Blockchain Technology: Towards a Better economic, and environmental sustainability in Malaysian Freight Transportation Sector - Yee Chew Fong (Universitas Internasional Batam, 2023)
Nowadays, maritime transport faces more challenges than at its beginning. Like any other industry, the maritime sector must adapt to the needs of the modern world and carry out its activities with respect for the environment. Continuous technological development and increased environmental awareness are the determining factors of changes in modern shipping. Therefore, one of the main challenges of maritime transport is to implement innovative solutions to protect the maritime environment. However, it is quite challenging to achieve both ecological and economic benefits at the same time. That is why it is very important to apply the win-win principle, which refers to the sustainable development of freight transportation. The paper provides an overview of applicable and promising technological solutions, and regulatory provisions towards a better economic, and environmental sustainability in Malaysian freight transportation sector, as well as importance of points to be considered in development of sustainable maritime.